The Effect of Survey Design on Household Reporting of Financial Difficulty - McKibbin, R; Breunig, R (My University, 2009)
We compare two Australian studies which ask households to report on the incidence of specific events of financial difficulty such as failure to pay the utility bill on time or seeking help from welfare agencies. While collected within the same year, the two studies use markedly different survey methodologies. One study uses a written self-completion questionnaire completed after a face-to-face interview, asks about individual experience of financial difficulty, and interviews each member of the household over the age of 15. The other study uses computer-assisted face-to-face interview and asks one randomly selected member of the household about household-level experience of financial difficulty. We find substantial differences in response rates, even after controlling for individual and household characteristics. The self-completion questionnaire elicits 30% more reports of financial difficulty for singles and 33% more for couple-headed households.
Economics Program, Research School of Social Sciences Working Paper
Keywords: Finance; Surveys and Survey Methodology; Finance -- Expenditure and constraints on expenditure; Surveys and Survey Methodology; Income, wealth and finances; Surveys and survey methodology; Finance; Surveys and Survey Methodology; Expenditure and constraints on expenditure; Income, wealth and finances; Surveys and Survey Methodology